P026 DEVELOPMENT OF A PREFERENCE-WEIGHTED SYMPTOM SCALE FOR INFLAMMATORY BOWEL DISEASE. (18th January 2018) - van Deen, Welmoed K; Obremskey, Alexandra; Polavarapu, Vivek; Moore, Graham; van den Akker-van Marle, M Elske; Doctor, Jason N; Hwang, Caroline
Abstract: Background: Practicing patient-centric care by incorporating patient preferences in IBD care is increasingly recognized to be important. However, existing IBD disease activity measures do not incorporate patient perspective. Here, we describe the development of a preference-weighted symptom score to evaluate treatment efficacy in IBD. Methods: We conducted three focus groups to understand which symptoms are most important for patients and why. Based on the results of the focus groups, we developed a choice-based conjoint (CBC) analysis survey to quantify the relative importance of identified symptoms. A preference-weighted score will be developed based on the results. To validate the results, the concordance between self-reported preferences and preferences obtained from the CBC analysis will be assessed. Results: We performed focus groups with 8 IBD patients in total. Three key-themes were identified that elucidate what makes symptoms important to patients: 1) symptoms that interfere with daily life; 2) symptoms that generate anxiety; or 3) symptoms that patients have no control over. Based on the results of the focus group, urgency, blood in the stool, abdominal pain and stool frequency were selected for inclusion in the CBC analysis. To date, 11 patients have filled out the CBC survey. An interim analysis of the survey found that – consistent with the focus group results – urgency is perceived to be the most important symptom, followed by abdominal pain, rectal bleeding, then stool frequency. As expected, more severe symptoms were perceived as more important. Self-reported preferences revealed that indeed, urgency was the most important symptom for 55% of patients. Conclusion: To fully quantify outcomes of IBD care based on the patient experience, we are developing a patient preference-weighted symptom score. This score will allow IBD researchers and practitioners to evaluate treatment efficacy while taking into account which symptoms matter to patients.